Vráble, Slowakei. Die Forschungen auf dem frühbronzezeitlichen Gräberfeld. Die Arbeiten seit 2015 - Stucky, Kerstin (e-Forschungsberichte des DAI, 2018)
Fidvár near Vráble displays an important Early Bronze Age site with extensive data on both the fortified settlement as well as the contemporary graveyard. From the beginning of the Middle Bronze Age onwards cremation burials emerge and inhumation burials, these comprehensive ‘archives’ of population biology start to disappear. Thus far, 43 Early Bronze Age graves have been excavated in Fidvár. Of this figure 40 were re-accessed, in most cases shortly after the burials took place. Further archaeological as well as anthropological, aDNA, and isotope analyses on this material will contribute to the interdisciplinary investigation into the question as to why prospering cultures in the Carpathian Basin met an unexpected and sudden end.